2015
DOI: 10.1002/polb.23922
|View full text |Cite
|
Sign up to set email alerts
|

Structure of poly(styrene‐b‐ethylene‐alt‐propylene) diblock copolymer micelles in binary solvent mixtures

Abstract: The effect of solvent selectivity on the micelle structure formed by a poly(styrene‐b‐ethylene‐alt‐propylene) diblock copolymer (PS‐PEP, MPS = 42,000 g/mol and MPEP = 62,000 g/mol) in solutions of squalane, a highly selective solvent for the PEP block, and 1‐phenyldodecane, a neutral solvent, is investigated using dynamic light scattering (DLS) and small‐angle X‐ray scattering (SAXS). The results reveal that addition of 1‐phenyldodecane systematically reduces solvent selectivity, leading to decreases in the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…18,19 Recently, Choi et al systematically investigated a series of PS-PEP diblock copolymers in pure squalane and binary solvent mixtures of squalane and 1-phenyldodecane, where 1-phenyldodecane is a less selective solvent than squalane. 20,21 In good agreement with observations by Quintana et al and Bang et al, the authors observed a smaller aggregation number, lower CMT, and higher solvent fraction in the core upon increasing the volume fraction of 1-phenyldodecane in binary solvent mixtures.…”
Section: ■ Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…18,19 Recently, Choi et al systematically investigated a series of PS-PEP diblock copolymers in pure squalane and binary solvent mixtures of squalane and 1-phenyldodecane, where 1-phenyldodecane is a less selective solvent than squalane. 20,21 In good agreement with observations by Quintana et al and Bang et al, the authors observed a smaller aggregation number, lower CMT, and higher solvent fraction in the core upon increasing the volume fraction of 1-phenyldodecane in binary solvent mixtures.…”
Section: ■ Introductionsupporting
confidence: 88%
“…20 Bang et al also showed no solvent in the core of PS-PI micelles in tetradecane at temperatures of 40 °C or more below T CMT . 18 We calculated T g wet assuming that the core composition is the same as the overall solvent composition (see above) using the volume fraction of binary mixed solvent in the core reported by Choi et al 20,21 and listed in Table 3. The estimated T g for the slightly solvated PS core would not change significantly with small variations in solvent composition due to the similar T g values of squalane and 1-phenyldodecane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, the nonselective solvent is removed from the solution with methods such as solvent evaporation or dialysis . This creates kinetically frozen micelles in the solution …”
Section: Introductionmentioning
confidence: 99%
“…Choi et al [ 56 ] studied the self-assembly of PS 404 - b -PEP 886 diblock copolymers in a mixture of 1-phenyldodecane (δ = 17.4 MPa 1/2 )/squalane (δ = 16.6 MPa 1/2 ). At 110 °C and a 50/50 ratio of 1-phenyldodecane/squalane, the micellar R h was equal to 280 nm, which is much higher than the value of 40 nm determined by Growney et al [ 41 ] for the PS 315 - b -PEP 1203 micelles in n -heptane, at the same temperature.…”
Section: Ab and Aba Linear Block Copolymers In Organic Solventsmentioning
confidence: 99%
“…If this requirement is not met, then a partition of the solvents may occur, which leads to a swelling of the micellar core by either one or both solvents in presence. A second possibility to use organic solvent mixtures in the self-assembly process of polyA- b -polyB copolymers was investigated by different authors [ 54 , 55 , 56 ]. Their approach consists in the solubilization of the copolymer in a common solvent S , a “ good ” solvent for both polyA and polyB sequences.…”
Section: Ab and Aba Linear Block Copolymers In Organic Solventsmentioning
confidence: 99%